Characterizing metabolomic and transcriptomic changes, and investigating the therapeutic mechanism of Psoralea corylifolia linn. In the treatment of kidney-yang deficiency syndrome in rats - Ming-Liang Zhang; Wei-Xia Li; Xiao-Yan Wang; Xiao-Fei Chen; Hui Zhang; Gao-Quan Meng; Yu-Long Chen; Ya-Li Wu; Liu-Qing Yang; Shu-Qi Zhang; Ke-Ran Feng; Lu Niu; et al. (Heliyon)
Kidney-yang deficiency syndrome (KYDS) is characterized by a metabolic disorder stemming from neuroendocrine dysregulation, often associated with hepatic dysfunction. In traditional Chinese medicine, Psoralea corylifolia Linn. (BGZ) is commonly utilized for treating KYDS. However, the specific therapeutic effects of BGZ on liver function regulation remain unclear. To evaluate the protective effects of BGZ against KYDS in rats, organ index, alanine aminotransferase (ALT), aspartate aminotransferase (AST), and other biochemical indices were analyzed. Hematoxylin and eosin (HE) staining was utilized to assess liver histopathology. Additionally, transcriptomic and metabolomic analyses were conducted to identify potential biomarkers. BGZ treatment led to a significant reduction in ALT and AST levels, accompanied by improvements in liver histopathology in rats with KYDS. Moreover, BGZ induced significant alterations in 92 differentially expressed genes (DEGs) and 20 metabolites in the KYDS rat model. The comprehensive examination of metabolites and DEGs identified potential mechanisms underlying the therapeutic effects of BGZ, highlighting the neuroactive ligand-receptor interaction, cAMP signaling pathway, calcium signaling pathway, and cytokine-cytokine receptor interaction as key mechanisms. Validation of key targets within the cAMP pathway was substantiated through enzyme-linked immunosorbent assay and real-time quantitative polymerase chain reaction. The cAMP pathway emerges as a plausible mechanism through which BGZ exerts protective effects against KYDS. The findings of this study contribute to an improved understanding of the therapeutic actions of BGZ and establish a groundwork for further research into the complex pathways involved, as well as the potential for drug-targeted therapies for KYDS.